Assessing the benefits and safety profile of incorporating poly ADP-ribose polymerase (PARP) inhibitors in the treatment of advanced lung cancer: a thorough systematic review and meta-analysis - Min Tang; Yue Wang; Pulin Li; Rui Han; Ran Wang (Frontiers Media S.A., 2024)
BackgroundPoly (ADP-Ribose) Polymerase (PARP) inhibitors represent a novel class of drugs that hinder DNA repair mechanisms in tumor cells, leading to cell death. This systematic review aims to evaluate the effectiveness, safety, and potential adverse effects of PARP inhibitors (PARPi) in the management of patients with advanced lung cancer.Materials and MethodsWe conducted a comprehensive search for relevant studies in PubMed, Embase, Cochrane, and ClinicalTrials.gov. We extracted primary and secondary outcome measures, including progression-free survival (PFS), overall survival (OS), and adverse events (AEs), from the identified literature for subsequent meta-analysis and systematic review.ResultsThis study encompassed twelve randomized controlled trials, involving 3,132 patients with advanced lung cancer. In comparison to non-PARPi treatments, the administration of PARPi significantly extended OS (hazard ratio (HR) = 0.90, 95% CI = 0.83-0.97, p = 0.006). However, the difference in PFS did not reach statistical significance.ConclusionIn summary, therapies incorporating PARPi provide a degree of benefit by extending OS in patients with advanced lung cancer. Nonetheless, further trials are necessary to furnish additional evidence regarding the efficacy and safety of PARPi in the treatment of lung cancer.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/, identifier number: CRD42023424673.